Transgenic expression of a functional fragment of harpin protein Hpa1 in wheat induces the phloem-based defence against English grain aphid - Fu, Maoqiang (Journal of experimental botany, 2014)
The harpin protein Hpa1 has multiple beneficial effects in plants, promoting plant growth and development, increasing crop yield, and inducing resistance to pathogens and insect pests. For these effects, the 10-40 residue fragment (Hpa1₁₀₋₄₂) isolated from the Hpa1 sequence is 1.3- to 7.5-fold more effective than the full-length protein. Here it is reported that the expression of Hpa1₁₀₋₄₂ under the direction of an insect-induced promoter induces the phloem-based defence to English grain aphid, a dominant species of wheat aphids. The expression of Hpa1₁₀₋₄₂ was found to compromise the colonization preference of aphids on the plant and further inhibit aphid reproduction in leaf colonies. In Hpa1₁₀₋₄₂-expressing wheat lines, moreover, aphid feeding from the phloem was repressed in correlation with the phloem-based defence. This defensive mechanism was shown as enhanced expression of wheat genes encoding phloem lectin proteins (PP2-A1 and PP2-A2) and β-1,3-glucan synthase-like enzymes (GSL2, GSL10, and GSL12). Both PP2-A and β-1,3-glucan formed high molecular mass polymers to block phloem sieve plate pores and therefore impede aphid feeding from the phloem. However, the phloem-based defence was impaired by treating plants with ethylene signalling inhibitors, suggesting the requirement for the ethylene signalling pathway. In addition, if Hpa1₁₀₋₄₂-expressing plants were subjected to attack by a small number of aphids, they newly acquired agriculturally beneficial characters, such as enhanced vegetative growth and increased tiller numbers and grain output values. These results suggest that the defensive and developmental roles of Hpa1₁₀₋₄₂ can be integrated into the germplasm of this agriculturally significant crop